The Effect of Arbuscular Mycorrhizal Fungi Inoculation in Mitigating Salt Stress of Pea (Pisum Sativum L.). Issue 11 (16th June 2020) - Parihar, Manoj; Rakshit, Amitava; Rana, Kiran; Tiwari, Gopal; Jatav, Surendra Singh
ABSTRACT: Salinity is one of the major threats to an agriculture production system and limits crop growth and productivity. Arbuscular mycorrhizal fungi (AMF) form a mutualistic association with majority of land plants and play important role in stress tolerance. In the present study, effect of three mycorrhizal treatments, i.e., single-species AMF ( Rhizoglomus intraradices), formulated AMF ( Funneliformis mosseae and R. intraradices ), and multispecies AMF ( Rhizoglomus fasciculatum and Gigaspora sp.) along with control (nonmycorrhizal) on growth, yield performance, and metabolic changes in pea crop under salinity stress was examined in completely randomized design with four replications. The results revealed that AMF inoculation mitigated negative effects of salinity in pea due to higher nutrient uptake, accumulation of compatible osmolytes, and lower cellular leakage of electrolyte which in turn enhanced biomass production, chlorophyll synthesis, yield, and growth attributes. Overall, consortium-based application of R. fasciculatum and Gigaspora sp. was found most suitable approach to ameliorate the salt stress in pea crop and enhanced the yield by 11%, 24%, and 54% than single-species, multispecies, and control treatments, respectively. The variation in results under different mycorrhizal treatment might be due to specific compatibility relationships that exist between symbionts.